Recovery of LiFePO4 cathodes: Criticalities and prospect towards a long-term eco-friendly solution - B. Visone; O. Senneca; P.P. Prosini; B. Apicella (Journal of Power Sources Advances)
Lithium iron phosphate batteries are currently getting increasing attention due to their low cost, good cycling stability and high safety characteristics. Enhanced batteries consumption is accompanied by their subsequent discard that, if poorly managed, may cause serious environmental damage as well as severe economic losses. Numerous cathode recycling techniques have been developed, including pyro/hydrometallurgical methods and direct regeneration.Besides providing information on the working and failing mechanism of these batteries, this review aims to present the most relevant spent cathode treatments, with an emphasis on environmental and economic implications. Moreover, it examines global regulations on lithium-ion battery recycling and identifies unresolved issues that still need to be addressed.Our analysis revealed that using organic acids significantly enhances the economic feasibility of hydrometallurgical processes, enabling for selective lithium recovery. This approach not only simplifies the procedure but also makes it more eco-friendly. Direct regeneration techniques, on the other hand, emerge as both economical and green alternatives to produce new cathodes with excellent electrochemical properties, but are difficult to apply due to the variability of the spent materials to be treated. Lastly, it appears imperative for legislators to formulate a regulatory framework specifically tailored to the treatment of spent lithium-ion batteries.